The Effect of Child-Friendly Problem Based Learning on the Science Learning Ability of Elementary School Students - Triyono Triyono; Eko Handoyo; Edi Waluyo (DIKODA JURNAL PENDIDIKAN SEKOLAH DASAR, 2026)
This research is motivated by the low learning ability of elementary school students in IPAS, which is caused by teacher-centered learning and the lack of student involvement in the learning process. This study aims to determine the effect of child-friendly Problem Based Learning on the IPAS learning ability of elementary school students. The research uses a quantitative approach with experimental research employing a One Group Pretest-Posttest Design. The research sample consisted of 15 fifth-grade elementary school students selected using purposive sampling. Data collection techniques were carried out through tests, observations, and documentation. The research instruments consisted of pretest and posttest questions on IPAS learning ability. The data were analyzed using the Paired Sample t-Test. Research results show that the average pretest score of the students was 64.8 with a score range of 48-82, while the average posttest score increased to 85.6 with a score range of 70-96. The statistical test results showed a p-value of 0.000, which is smaller than the significance level of 0.05, indicating a significant effect of child-friendly Problem Based Learning on elementary school students' science learning abilities. This learning model can be used as an alternative innovative, active, and enjoyable approach in the learning process at elementary schools.